Integrating Deep Learning to Foster Meaningful and Joyful Learning in Quranic Studies: A Merdeka Curriculum Framework - Paimin Paimin; Imam Syafi’i; Jaenullah Jaenullah (CV. Bimbingan Belajar Assyfa, 2026)
The implementation of the Merdeka Curriculum in Islamic education demands a pedagogical shift from rote memorization to profound conceptual understanding, yet many Quranic studies classrooms still struggle with disengagement and superficial learning. This study aims to analyze the integration of the Deep Learning approach—characterized by mindful, meaningful, and joyful learning—within the Al-Qur'an Hadith subject at Madrasah Tsanawiyah. Using a qualitative case study design, data were gathered through in-depth interviews, participant observation, and documentation at MTs Mathla’ul Anwar Landbaw. The findings reveal that instructional planning aligns with KMA No. 1503 of 2025, emphasizing a